The Role of Establishing Neurosurgical Specialist Nurse Working Group in the Recovery and Prevention of Negative Psychological Emotion after Meningioma Surgery. (27th June 2022) - Luo, Zhen; Yang, Qiaoyu; Tang, Min; Fan, Chaofeng
Abstract : In this research paper, we will explore the role of establishing a neurosurgical specialist nurse working group in the recovery and prevention of negative psychological emotions after meningioma surgery. For this study, 42 meningioma patients who were treated before the establishment of a neurosurgery specialist nurse working group from January 2019 to December 2019. They were selected as the control group. In contrast, 42 meningioma patients admitted after the establishment of the neurosurgery specialist nurse group from January 2020 to December 2020 were selected as the study group. The postoperative recovery (time of stay in the intensive care unit, time of first eating, wakeup time, time of defecation for the first time, and hospitalization time), short-term prognosis, and nursing satisfaction scores of the two groups were calculated, and the post-traumatic stress disorder scale (PTSD-SS), medical coping style questionnaire (MCMQ), and National Institutes of Health Stroke Scale (NIHSS) were compared. Also, the changes in the self-rating anxiety scale (SAS) and self-rating depression scale (SDS) score contributes to the comprehensive analysis of the role of the establishment of neurosurgical specialist nurse working group in the recovery and prevention of negative psychological emotion after meningioma operation. The satisfaction scores in the study group of patients in physical care, receiving information, support, respect, and nursing process were higher than the control group probability (P < 0.05 ). The first feeding time, defecation time, out of bed, the stay time in the intensive care unit, and the hospitalization time of the study group were shorter than those of the control group (P < 0.05 ). Before nursing, there was no difference in NIHSS score, SAS score, and SDS scores between the two groups. However, after nursing, the NIHSS score, SAS score, and SDS score of the study group were fairly lower than the control group. Moreover, the Karnofsky functional status scale (KPS) scores of the two groups increased gradually. The KPS scores of the study group at 1 month, 2 months, and 3 months after operation were significantly higher than those of the control group (P < 0.05 ). Before nursing, there was no significant difference in the scores of post-traumatic stress disorder between the two groups (P > 0.05 ). After nursing, the scores of subjective evaluation, symptom avoidance, repeated experience, and social dysfunction in the study group were lower than those in the control group (P < 0.05 ). Before nursing, there was no significant difference in coping scores between the control group and the research group (P > 0.05 ), but after nursing, the avoidance and compliance scores of the research group were significantly higher than those of the control group (P < 0.05 ).Similarly, the scores of avoidance and yield in the study group were significantly lower than those in the control group (P < 0.05 ). In the study group, 1 patient had an incision infection and 1 patient had epilepsy, and the total incidence of postoperative complications was 4.76%. In the control group, 4 patients had incision infection, 1 case of an intracranial hematoma, 3 cases of deep venous thrombosis, and 3 cases of epilepsy. The total incidence of postoperative complications in the study group was 26.19%, while the incidence of postoperative complications in the study group was lower than in the control group (P < 0.05 ).